THE IMAGE OF LOVE IN THE SUFI DOCTRINE OF ALISHER NAVOI (CAHIERS MAGELLANES-NS, 2024)
The article reveals the image of a lover in the Sufi teachings of Alisher Navoi. In Sufi terminology, God was called the Beloved and the Beauty, and the Sufi contemplating the Beloved was called the lover, Majnun. Worship of the Almighty was called passion and love. The curls and mole of the Beloved are the attributes of his beauty. Sufi love has a kind of outcome - sukra and sahw. Sahw is characterized as a dive in the sea and an exit with pearls, or a flight to heaven and, when flying back to earth, remember one's duties, etc. That is, a person who knows the Truth teaches a lesson to others. Sukra - intoxication, madness (Majnun) with love. Everything is in the will of God and it is necessary to ask him for the good of salvation. It is impossible, Navoi believes, for the love of God to obscure human love, which has the right to exist, it is necessary, but should not be the goal of life. This is how bioenergetics think today.